2013
DOI: 10.1007/s00702-013-1023-z
|View full text |Cite
|
Sign up to set email alerts
|

Movement disorders in systemic lupus erythematosus and the antiphospholipid syndrome

Abstract: Movement disorders (MDs), particularly chorea, may be the presenting neurological complication of systemic lupus erythematosus (SLE) and the antiphospholipid syndrome (APS), but the association is not often initially recognized. Current evidence suggests an autoimmune mechanism related to antiphospholipid antibodies in these two conditions, although the antigenic target within the central nervous system has not yet been identified. Based on a comprehensive review of the literature, this article summarizes the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
1
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(66 citation statements)
references
References 117 publications
1
56
1
4
Order By: Relevance
“…In a series of 41 patients with SLE, the authors identified 4 patients with movement disorders (2 with parkinsonism and 1 each with myoclonus and chorea) 45. Of clinical relevance is the finding that chorea may precede the onset of other findings of SLE in up to 22% of patients 46. In our own centre a systematic and careful evaluation of 54 consecutive patients with SLE we found that movement disorders were rare, 1 patient had chorea and the other one, parkinsonism.…”
Section: Sle and Related Conditionsmentioning
confidence: 99%
“…In a series of 41 patients with SLE, the authors identified 4 patients with movement disorders (2 with parkinsonism and 1 each with myoclonus and chorea) 45. Of clinical relevance is the finding that chorea may precede the onset of other findings of SLE in up to 22% of patients 46. In our own centre a systematic and careful evaluation of 54 consecutive patients with SLE we found that movement disorders were rare, 1 patient had chorea and the other one, parkinsonism.…”
Section: Sle and Related Conditionsmentioning
confidence: 99%
“…Nonetheless, parkinsonism, myoclonus and dystonia were described and an autoimmune or thromboembolic disease mechanism has been proposed for their occurrence 39 . Chorea is the most described manifestation and may be the first manifestation in SLE occurring in 2% of adult patients, predominantly in women.…”
Section: Movement Disordersmentioning
confidence: 99%
“…It can be unilateral or bilateral and remit spontaneously. Current evidence suggests an autoimmune mechanism related to aPL antibodies, but focal cerebral ischemia is rarely evidenced 39 . Sydenham chorea is the most common cause of acute chorea in children and it is one important differential diagnosis in chorea associated with lupus, especially in pediatric patients.…”
Section: Movement Disordersmentioning
confidence: 99%
“…Symptoms may improve during sleep or in a supine position. Huntington's disease, Wilson's disease, prion diseases, Sydenham chorea, systemic lupus erythematosus, antiphospholipid antibody syndrome, anti-N-methyl-D-aspartate receptor encephalitis and other autoimmune diseases as illustrated [31][32][33][34][35] in Table 6. The workup may include selected laboratory studies, as well as imaging modalities such as CT, MRI or positron emission tomography (PET).…”
Section: Akathisiamentioning
confidence: 99%